Surface plasmon enhanced F?rster resonance energy transfer between the CdTe quantum dots - Gounko, Iouri; Bradley, Louise (My University, 2008)
Forster resonance energy transfer (FRET) between CdTe quantum dots (QDs) at nanoscale proximity to gold nanoparticle (Au NP) layers is investigated experimentally. We have observed the enhancement in the acceptor QDs' photoluminescence lifetime intensities. The decrease in donor QDs' exciton lifetime from 5.74 to 2.06 ns, accompanied by an increase in acceptor QDs' exciton lifetime from 3.38 to 7.52 ns, provided evidence for enhanced FRET between the QDs near Au NPs. The Au NPs' surface plasmon dipole fields are assisted to overcome the weak electronic coupling between the emitting (donor) and absorbing (acceptor) transition exciton dipoles in the homogeneous medium
PUBLISHED
This paper was selected for inclusion in the Virtual Journal of Nanoscale Science and Technology 18, 4 (2008).
Keywords: Physics; Nanoscience & Materials